Potential of APOBEC3B as a therapeutic target and its role in bladder cancer onset and progression - Zexi He; Chen Gong; Jun Gu; Wei Wang; Haihao Li; Zhiyong Tan; Haifeng Wang; Jiansong Wang; Mingxia Ding; Yinglong Huang (European Journal of Medical Research)
Abstract Background This investigation aims to investigate the impact of apolipoprotein B mRNA editing enzyme catalytic polypeptide 3B (APOBEC3B/A3B) on the malignant biological characteristics of bladder cancer. Additionally, the study examines the potential mechanisms of APOBEC3B’s action to assess its feasibility as a therapeutic strategy for bladder cancer. Methods The investigation first confirmed APOBEC3B expression in bladder cancer using bioinformatics and experimental validation. Then, the relationship between APOBEC3B expression and various parameters was analyzed, with gene set enrichment analysis (GSEA) to explore pathways. The IMvigor210 cohort was analyzed to validate the correlation between APOBEC3B expression and immunotherapy efficacy. Results Cellular and animal experiments further validated the impact of APOBEC3B on bladder cancer biology. High APOBEC3B expression in bladder cancer patients is associated with an increased frequency of somatic mutations. APOBEC3B expression levels are significantly correlated with the infiltration of various immune cells and the expression of immune checkpoint-related genes. Moreover, high APOBEC3B expression is associated with increased tumor mutation burden. In the IMvigor210 cohort, APOBEC3B expression is significantly upregulated in individuals with positive responses to immunotherapy. Our study suggests that APOBEC3B plays a key role in promoting the initiation and progression of bladder cancer. Additionally, bladder cancer cells with overexpressed APOBEC3B can enhance the polarization of M2-like tumor-associated macrophages. Conclusion The research demonstrates that APOBEC3B exhibits high expression levels in bladder cancer and can enhance its malignant biological behavior. APOBEC3B may serve as a promising therapeutic target in future treatments.